Influence of repetitively-pulsed plasma immersion low energy on implantation to tin coating properties formation; Energy Fluxes and Radiation Effects (EFRE-2016) - Sivin D. O. Denis Olegovich; Ananin P. S. Petr Semenovich; Dektyarev S. V. Sergey Valentinovich; Ryabchikov A. I. Aleksandr Ilyich; Shevelev A. E. Aleksey Eduardovich; Korneva O. S. Olga Sergeevna (2016, 2016)
Title screen